SEJARAH LEMBAGA PENDIDIKAN ISLAM DAN PERKEMBANGANNYA DI INDONESIA - Ghassany, Haidar Rifqi; Mun'im, Muhtadi Abdul (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
The rapid development of Islam in Indonesia since its inception until now cannot be separated from the role of Islamic Religious Education institutions. If you look at the beginning of the entry of Islam into Indonesia in the 13th century through trade and da'wah of merchants from the Middle East and Gujarat, Islamic educational institutions have undergone several changes in name or form. Consequences of changes in social conditions and the development of science and technology starting from Islamic education still uses the Hindu education pattern, the establishment of educational institutions based on Islamic technology today. Among the classical Islamic educational institutions that still exist to now including Surau, Dayah, Islamic Boarding School, meunasah, Madrasah, and others. Exist several Islamic educational institutions that are no longer found, there are several still standing but experiencing a decline in function that managed to survive by adapting to the guidance of the era. One of the institutions of classical Islamic education is able to develop in accordance with The development of the times is a boarding school. This is evidenced by the existence of Islamic boarding schools with a variety of special sciences that are integrated with Islamic educational values.